(6x+4)+(7x-2)=

Simple and best practice solution for (6x+4)+(7x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+4)+(7x-2)= equation:


Simplifying
(6x + 4) + (7x + -2) = 0

Reorder the terms:
(4 + 6x) + (7x + -2) = 0

Remove parenthesis around (4 + 6x)
4 + 6x + (7x + -2) = 0

Reorder the terms:
4 + 6x + (-2 + 7x) = 0

Remove parenthesis around (-2 + 7x)
4 + 6x + -2 + 7x = 0

Reorder the terms:
4 + -2 + 6x + 7x = 0

Combine like terms: 4 + -2 = 2
2 + 6x + 7x = 0

Combine like terms: 6x + 7x = 13x
2 + 13x = 0

Solving
2 + 13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 13x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 13x = 0 + -2
13x = 0 + -2

Combine like terms: 0 + -2 = -2
13x = -2

Divide each side by '13'.
x = -0.1538461538

Simplifying
x = -0.1538461538

See similar equations:

| 5-7=3x-5x | | -2(4s-6)-12=-3(4s+3)-3 | | 2(3h-2)=14 | | 2x-8x=-5 | | 2(x-3)=2x+4 | | -(w+5)=14 | | 9a^3+15a^2-36a=0 | | -3(5s-4)-12=2(9s+7)-2 | | 42x^2-15x-3=0 | | -2(-3x-w)-(2w-6x)= | | 5x^2+6x=12x-9 | | 8(x+2)=8x+16 | | 0.25x+.05(2-x)=.10(37) | | -5(x-4)=40 | | 8(x+6)-3(2x-7)=127 | | 1=d/10-12 | | 24v^2-9v+32v-12=0 | | 5y=-2.8 | | 7n-1=9+10n-12 | | 3x^2+2x-5=2x^2-2 | | 0.5=-8 | | 0.36(6)+0.04x=0.12(18+x) | | 4(6a-16)+2(2a+12)=4 | | 0.41x=8.2 | | -3(3y+v)+6(4v-4y)= | | 24-4(7-2t)=4(t-1) | | 950=25h+40 | | 1/2=-8 | | c=25h+40 | | -(2x+5)-9x= | | -x-2y=8 | | 3*32*3+u=(3*3*3-3*8)(2)+u |

Equations solver categories